2007
DOI: 10.1037/0278-7393.33.4.720
|View full text |Cite
|
Sign up to set email alerts
|

How abstract is symbolic thought?

Abstract: In 4 experiments, the authors explored the role of visual layout in rule-based syntactic judgments. Participants judged the validity of a set of algebraic equations that tested their ability to apply the order of operations. In each experiment, a nonmathematical grouping pressure was manipulated to support or interfere with the mathematical convention. Despite the formal irrelevance of these grouping manipulations, accuracy in all experiments was highest when the nonmathematical pressure supported the mathemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
153
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(178 citation statements)
references
References 56 publications
22
153
2
1
Order By: Relevance
“…This pattern of alignments suggests that people view the symbolic notations of rational numbers as either discrete (fractions) or continuous (decimals). Although this hypothesis has yet to be tested directly (e.g., by asking people to select continuous or discrete representations for numbers without specifying their units), it is consistent with recent work showing the impact of notational tools on mathematical reasoning (Braithwaite & Goldstone, 2013;Fisher, Borchert, & Bassok, 2011;Landy & Goldstone, 2007;Zahner & Corter, 2010).…”
Section: Discussionsupporting
confidence: 77%
“…This pattern of alignments suggests that people view the symbolic notations of rational numbers as either discrete (fractions) or continuous (decimals). Although this hypothesis has yet to be tested directly (e.g., by asking people to select continuous or discrete representations for numbers without specifying their units), it is consistent with recent work showing the impact of notational tools on mathematical reasoning (Braithwaite & Goldstone, 2013;Fisher, Borchert, & Bassok, 2011;Landy & Goldstone, 2007;Zahner & Corter, 2010).…”
Section: Discussionsupporting
confidence: 77%
“…In our study, instead of content (e.g., objects, story line) the surface cue was the format of the algebraic equations. In some respects, college students' tendency to follow the linear layout of standard-form algebraic models (i.e., engage in direct translation of word to equations) is similar to recent findings of Landy and Goldstone (2007). These researchers found that the physical layout of algebraic equations affects the way college students apply a well-known mathematical rule.…”
Section: Discussionsupporting
confidence: 73%
“…No such difference, however, was found for students who has been taught algebra with a representation system which eliminated these saliency features. Complementary results were published by Landy and Goldstone (2007), who found that the internal spacing of algebraic expressions can affect their opaqueness/transparency.…”
Section: The Affirmative Premise Effectsupporting
confidence: 67%